The Non-Ratification of the 1951 Convention on Refugees: An Indian Paradoxical Approach to Human Rights - Boutier, Indira (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2021)
The following paper explores the position of India on refugees and its resistance to signing the 1951 Convention Relating to the Status of Refugees. It first revisits the colonial frame in which a refugee policy was thrust upon the country. Secondly, it analyzes the geopolitical and internal constraints that determined India’s approach to the refugee question in the 1950s. Finally, it focuses on the current moment to discuss the implications of the recent amendment of the Citizenship Act for refugees in India. Such a long-term approach can open the door to a process of accommodation both by international organizations and by national governments around some universal humanitarian principles that must govern refugee policies. States remain sovereign in their international commitments. They choose to ratify a treaty or not, and to denounce it or not. In addition, human rights institutions are regularly criticized and attacked by States while their legitimacy is often questioned. It is this sovereign freedom of each State, which makes this matter difficult to grasp. We believe that understanding the factors influencing States in their choices is particularly crucial in this period of instability in international relations.